2006
DOI: 10.1111/j.1349-7006.2006.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of endometrial stromal sarcoma of the uterus

Abstract: Endometrial stromal sarcoma (ESS) of the uterus is a rare uterine malignancy that has not been characterized in detail. To characterize the phenotype of ESS of the uterus, we extracted RNA from ESS and the stroma of normal endometrium using a tissue microdissection system and compared the expression profiles in the two tissues. After suppression subtractive hybridization and differential screening, we detected the metastasis-associated lung adenocarcinoma transcript 1 (MALAT-1) gene as one of the major genes u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 21 publications
2
80
0
Order By: Relevance
“…Indeed, a chromosomal translocation of t(6;11)(p21.1;q13) is observed for primary renal tumors that results in the fusion of the alpha gene with TFEB, a basic helix-loop-helix leucine zipper (bHLH-LZ) transcription factor (Davis et al, 2003), and upregulation of TFEB protein levels owing to promoter substitution (Kuiper et al, 2003). Expression of the MALAT-1 gene was also increased in the metastasizing non-small-cell lung cancer compared with the non-metastasizing tumors (Ji et al, 2003), and also upregulated in endometrial stromal sarcoma compared with the stroma of normal endometrium (Yamada et al, 2006). These observations, in combination with our current study identifying MALAT-1 as a potentially generic marker for carcinomas, suggest the significant role of MALAT-1 in the molecular events of neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a chromosomal translocation of t(6;11)(p21.1;q13) is observed for primary renal tumors that results in the fusion of the alpha gene with TFEB, a basic helix-loop-helix leucine zipper (bHLH-LZ) transcription factor (Davis et al, 2003), and upregulation of TFEB protein levels owing to promoter substitution (Kuiper et al, 2003). Expression of the MALAT-1 gene was also increased in the metastasizing non-small-cell lung cancer compared with the non-metastasizing tumors (Ji et al, 2003), and also upregulated in endometrial stromal sarcoma compared with the stroma of normal endometrium (Yamada et al, 2006). These observations, in combination with our current study identifying MALAT-1 as a potentially generic marker for carcinomas, suggest the significant role of MALAT-1 in the molecular events of neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, MALAT-1 overexpression is a prognostic parameter for poor NSCLC patient survival and can be used to identify early-stage NSCLC patients who are at risk to develop metastases. In addition to NSCLC, recent studies have also reported the overexpression of MALAT-1 in uterine endometrial stromal sarcoma and hepatocellular carcinoma Yamada et al 2006). Another ncRNA gene, NCRMS (noncoding RNA in RMS), shows elevated expression in alveolar rhabdomyosarcoma (RMS) but not in the embryonal subtype of RMS (Chan et al 2002).…”
Section: Linking Ncrna and Cancermentioning
confidence: 99%
“…Recent studies show that MLATA1 is also overexpressed in breast cancer, prostate tumors, rectal carcinoma, HCC, and cervical cancer (Lin et al, 2007;Guo et al, 2010). In addition, a number of reports have demonstrated that MLATA1 overexpression is linked to cancer metastasis (Yamada et al, 2006). Recent studies have also revealed that lncRNAs exhibit different patterns of expression in different types of tumors.…”
Section: Discussionmentioning
confidence: 99%